Exploring Potential Protective Factors for the Relationship between Low Self-Control in Adolescence and Negative Health Outcomes in Adulthood - Boccio, Cashen M. (International journal of offender therapy and comparative criminology, 2021)
Previous research links low levels of self-control with criminal involvement and negative life outcomes. A similar line of inquiry has begun to explore whether low levels of self-control are also associated with developing health problems in adulthood. This paper extends this research by examining associations between adolescent levels of self-control and four different categories of health outcomes in adulthood. In addition, this study examines whether associations between adolescent levels of low self-control and health outcomes in adulthood are moderated by environmental protective factors. The results reveal that low levels of self-control in adolescence are consistently associated with reporting more health problems. In addition, some evidence emerged in support of the role of environmental protective factors in buffering the risk of developing health problems conferred by low levels of self-control in adolescence.